Ensuring quality and safety in the production and storage of grain crops - Talgat Kulazhanov; Raushangul Uazhanova; Lyazzat Baybolova; Yerkin Yerzhigitov; Aliya Kemerbekova; Kamilya Tyutebayeva; Assel Izembayeva; Sholpan Zhengiskyzy (Caspian Journal of Environmental Sciences)
Grains are one of the countries' strategic products and the primary protein supply source in society. This study describes the qualitative and safety aspects of grains. Grain storage and preservation is a complex and active process, because after harvesting, grains can also perform all apparent vital functions, such as respiration, metabolism, and growth, as a living organism, and are subject to chemical and biological changes such as reduced strength, increased acidity, gluten weakening, enzymatic decomposition, loss of nutrients and apparent changes such as breakage and perforation and germination. On the other hand, losses due to grain handling, losses due to natural drying and moisture loss of grains, and losses related to the activity of microorganisms or the activity of storage pests are among the factors that will lead to a quantitative and qualitative loss of grains during storage. This study evaluated the standard for harvesting and preserving grains in Kazakhstan, and its qualitative classification has been carried out. The results show that moisture content, harvesting, packaging, and aeration are among the main factors in grain safety. In general, the main goal during storage and warehousing is to maintain the quantity and quality of grains so that the main properties of the grain are preserved during storage, and its change is prevented. Therefore, it is necessary to control moisture, temperature, contamination by storage pests, and the internal activity of grains, which are living structures.